ÅPuede destaparse la caja negra de la junta directiva? : un análisis del Groupthink a partir de la diversidad en las juntas y el desempeño financiero (2017)
"This document attempts to find evidence of groupthink in the relation between variables of composition and features of board of directors of american companies, and their respective financial performance during 2015, as a measure of fulfillment of strategic functions. Analyses show results supporting groupthink given a negative impact of experience diversity and average tenure of board members on financial performance (ROA). The results, first, allow to interpret an adverse effect of experience diversity on performance, in a scenario where no agreements are reached, and there is a false consensus typical of groupthink, leading to unfavorable results; second, results support group cohesion as an antecedent of groupthink, based on a high tenure of board members as an element that impacts performance negatively." -- Tomado del Formato de Documento de Grado.